N-Doped Graphene Oxide as Additive for Fumed Silica Based Gel Electrolyte of Valve Regulated Lead Acid Batteries - Mansuroglu, Abdulmecit; Arvas, Melih B.; Kiraz, Caner; Sayhan, Barishan; Akgumus, Alperen; Gencten, Metin; Sahin, Mutlu; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2021)
In this work, nitrogen doped graphene oxide powder (N-GrOP) was used as an additive for fumed silica based gelled electrolyte of valve regulated lead acid (VRLA) batteries for the first time in the literature. Optimum amount of additive was determined as 0.4 wt% N-GrOP by using of electrochemical methods and corrosion tests. The structural features of fumed silica based gelled electrolyte with and without N-GrOP was investigated by SEM analysis. Then, the effects of agitation time and stirring rate on the formation and structure of the fumed silica based gelled electrolyte were optimized as 180 min and 1250 rpm, respectively, by using of electrochemical technics. Corrosion tendency of the electrodes were determined by Tafel curves. Cyclic charge/discharge tests were also carried out to determine the discharge capacity of the electrolytes. The discharge capacities of fumed silica based gelled electrolyte with and without N-GrOP and non-gelled electrolyte were determined as 33 mAh.cm(-2), 16 mAh.cm(-2) and 0.70 mAh.cm(-2) at 20 mA.cm(-2) charge/discharge current densities, respectively. The interaction of N-GrOP with hydrolyzed fumed silica particles occurred and the discharge capacities of the fumed silica-based gel electrolyte increased in VRLA batteries.
Keywords: ENERGY-STORAGE; POSITIVE ELECTRODE; CYCLIC VOLTAMMETRY; FLOW BATTERY; COATED LEAD; PERFORMANCE; NANOSHEETS; REDUCTION; MECHANISM; BEHAVIOR; Electrochemistry; Materials Science